A feasibility study of the Coulter S Plus II cytogram replacing the conventional differential for monitoring a patient's clinical progress. - Nelson, Lydia (My University, 1983)
This hematologic study was performed to evaluate the feasibility of the Coulter S Plus IIᴿ cytogram, with lymphocyte percent and lymphocyte number, replacing the conventional differential for monitoring a patient's clinical progress. The Coulter S Plus II had excellent correlation with manual lymphocyte percent counts (r=0.939) and automated lymphocyte percent counts (r=0.921). The S Plus II cytogram was also found to be an effective screening method for abnormal blood cells. Both manual and automated band neutrophil counts, which are traditionally used by physicians to monitor clinical progress, were found to bevariable, position dependent, poorly reproducible, and affected by toxic granulation when counted by a pattern recognition method. When S Plus II electronic differentials were made available to the medical and surgical intensive care units of Johns Hopkins Hospital, there was a 92% reduction in differential requests. A review of 191 hospitalized patients' charts revealed no difference in monitoring patients' clinical progress using the Coulter S Plus II lymphocyte counts or the manual differential band counts. The findings of this study indicate that upon hospital admission, a patient should receive a complete blood count, 200 cell differential, plus a 100 cell anning differential, red cell morphology, and platelet evaluation. After the initial evaluation, patients without complications, can be monitored with the Coulter S Plus II cytogram with lymphocyte percent and lymphocyte number, instead of the conventional differential.